Research methods for business : a skill-building approach - Sekaran, Uma.; Bougie, Roger (Chichester : John Wiley & Sons, 2009)
'Research Methods for Business: A Skill Building Approach is a concise and straightforward introduction for students to the world of business research. The skill building approach provides students with practical perspectives on how research can be applied in real business situations. Maintaining Uma Sekaran's popular and accessible style of writing, Roger Bougie draws upon his extensive experience of the field to present an up-to-date guide on business research for the aspiring future manager.''The fifth edition has a new chapter on qualitative data analysis, featuring a case study of the research process. The chapters on scientific investigation, the broad problem area and defining the problem statement, measurement of variables, experimental designs, sampling, and quantitative data analysis have all been substantially revised. Additional real-life cases have been included and examples are taken from Europe, Asia and the US to give students a comprehensive view of modern business research methods.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Business -- Research -- Methodology